2020
DOI: 10.1371/journal.pone.0244365
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and transcriptomic analyses of yellow horn (Xanthoceras sorbifolia) provide important insights into salt and saline-alkali stress tolerance

Abstract: Yellow horn (Xanthoceras sorbifolia) is an oil-rich woody plant cultivated for bio-energy production in China. Soil saline-alkalization is a prominent agricultural-related environmental problem limiting plant growth and productivity. In this study, we performed comparative physiological and transcriptomic analyses to examine the mechanisms of X. sorbifolia seedling responding to salt and alkaline-salt stress. With the exception of chlorophyll content, physiological experiments revealed significant increases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 84 publications
1
25
0
Order By: Relevance
“…There is a reason to suggest that for typical high salt-adapted species native to saline habitats (halophytes) high level of K + in substrate will have the same negative effects than Na + [ 9 ]. It was also shown that for halophytes, NaCl toxicity is related mainly to the effect of Cl – [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a reason to suggest that for typical high salt-adapted species native to saline habitats (halophytes) high level of K + in substrate will have the same negative effects than Na + [ 9 ]. It was also shown that for halophytes, NaCl toxicity is related mainly to the effect of Cl – [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported on the effect of salt stress on leaves and roots, and their results revealed that salt stress exerted distinct effects on growth, photosynthesis, membrane permeability, osmotic adjustment substance, enzyme activity, and so on (Sorkheh et al, 2012 ; Kargbo et al, 2019 ; Yang et al, 2020 ). In addition, researchers have provided important insights into salt and saline-alkali stress tolerance of yellow horn ( X. sorbifolium ) on physiological and transcriptomic levels (Wang et al, 2020 ). In the study, Zhang X. Y. et al ( 2013 ) compared the effects of five concentrations of sodium chloride (NaCl) on X. sorbifolium , and it was found that the plant could alleviate the osmotic stress induced by NaCl solution, proving the salt tolerance of the species.…”
Section: Introductionmentioning
confidence: 99%
“…TFs receive stress signals and bind to cis-regulatory sequences to regulate downstream gene expression [ 49 , 50 , 51 , 52 ]. In soybean, GmMYB68 overexpression enhanced salt–alkali resistance in transgenic plants [ 18 ].…”
Section: Discussionmentioning
confidence: 99%